1999
DOI: 10.1063/1.125266
|View full text |Cite
|
Sign up to set email alerts
|

The use of the in-field critical current density, Jc(0.1 T), as a better descriptor of (Bi, Pb)2Sr2Ca2Cu3Ox/Ag tape performance

Abstract: Extended voltage-current characteristics of 13 optimized ͑Bi, Pb͒ 2 Sr 2 Ca 2 Cu 3 O x /Ag multifilamentary tapes from four different manufacturers were extensively evaluated so as to extract the field-dependent J c (H), the characteristic field H p obtained from the relation J c ϳexp (ϪH/H p ), and the irreversibility field H*. Values of the self-field critical current density J c (0 T, 77 K) ranged from 12 to 63 kA/cm 2 , I c (0 T,77 K) from 11 to 139 A, H p from 128 to 204 mT, and H* from 163 to 369 mT, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…A strong correlation between and is found. As reported previously [12], the curves of Bi-2223 tape exhibit an exponential form above the self-field and weak-link dominated region, , where the characteristic field characterizes the in-field performance. As listed in Table I, increased from 126 mT for TA-3 to 183 mT for TA-5.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…A strong correlation between and is found. As reported previously [12], the curves of Bi-2223 tape exhibit an exponential form above the self-field and weak-link dominated region, , where the characteristic field characterizes the in-field performance. As listed in Table I, increased from 126 mT for TA-3 to 183 mT for TA-5.…”
Section: Resultssupporting
confidence: 79%
“…Measurements of critical current ( ) were made in liquid nitrogen in a 1 Tesla electromagnet with the magnetic field applied perpendicular to the broad tape surface, making nominally parallel to the axis [12]. The criterion for is 1 V cm and was defined as , where is the average of two or three Bi-2223 cross-section measurements.…”
Section: Methodsmentioning
confidence: 99%
“…For Bi-2223 tapes there is also a region from about 50 mT to 150 mT for which is proportional to [3]. We report this decrement field, , as a second benchmark of tape quality.…”
Section: Methodsmentioning
confidence: 86%
“…Careful study of tapes from multiple sources by transport has shown that (77 K) as measured by can vary significantly from 160 to 370 mT [3]. In principle, a higher is taken to be evidence of stronger flux pinning, a highly desirable property that would be even more valuable in the 25-50 K range where Tesla-strength magnetic field applications for 2223 can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Because the self-field significantly suppresses the of highcurrent Bi-2223 tapes at 77 K [6], [7], performance levels are now quantitatively measured in an applied field of 0.1 T (//c) to determine intrinsic material performance. The value of 22 100 A cm at 77 K and 0.1 T (//c) from the new experimental wire reported here is 10 higher than the level obtained last year [2], 30% higher than the estimated 0.1 T value for AMSC's self-field record tape (74 kA cm , 77 K, made in 1998) [4], and represents a new level of performance for MFC wires.…”
Section: Resultsmentioning
confidence: 99%